Use of Tumor Marker and Enzymes in Recurrence and Monitoring Response to Pre and Post Chemotherapy for Patients with Upper Gastrointestinal Carcinoma - Ambad, Ranjit S. (International Journal of Innovative Research in Medical Science, 2017)
Aim - To analyze the level of serum Carcinoembryonic antigen (CEA) Glutathione-S-Transferase (GSTs), Lactate Dehydrogenase (LDH) and Alkaline Phosphatase (ALP) before and after different cycles of chemotherapy in reference to upper gastrointestinal cancer patients. Methods - For the study comprising total 232 cases suffering from gastrointestinal cancer (before and after different cycles of chemotherapy) were selected. All patients were clinically and histopathologically diagnosed. A total of 42 age and sex matched healthy subjects taken as control. The circulating levels of CEA, GSTs, LDH and ALP activity were assayed in the in the serum of control group and in patients with gastrointestinal cancer. Results - Mean CEA, GSTs, LDH and ALP activity in serum were significantly higher in gastrointestinal cancer patients as compared to normal control group (p<0.001). After first chemotherapy (stage II) the activity of GSTs, LDH and ALP were significantly higher but the activity of CEA was highly significantly decreased than before chemotherapy (stage I). In stage III (after second cycle of chemotherapy) activity was significantly decreased than that of stage II and the activity of CEA, GSTs, LDH and ALP was significantly decreased in stage IV (after third cycle of chemotherapy) than stage III (after second cycle of chemotherapy) and levels become normal in range. Conclusion - The study highlights serum CEA and GSTs measurement are useful marker for gastrointestinal cancer, its activity helpful to predict the response of treatment in advanced stage of cancer and recurrence of disease. Increased levels of serum LDH and ALP indicates infection or blockage or metastasized or liver damage by treatment. LDH and ALP are good prognostic marker in gastrointestinal cancer treated with chemotherapy. Increased level of ALP indicates advanced disease progression or treatment strategy. Statistically significant changes in CEA, GSTs, LDH and ALP levels during the treatment with positive response and no established disease progression during study period near about 27 months after the treatment, which indicate that GSTs and CEA are important predictive factor.